Resveratrol attenuated hydrogen peroxide-induced myocardial apoptosis by autophagic flux - Huang, Chih-Yang (Food Nutr Res, 2016)
BACKGROUND: Resveratrol is a Sirt-1-specific activator, which also exerts cardioprotective effects that regulate redox signalling during oxidative stress and autophagy during cardiovascular disease (CVD). OBJECTIVE: This study investigated the protective effects of resveratrol against hydrogen peroxide-induced damage in cardiomyocytes. DESIGN: In this article, hydrogen peroxide-induced autophagy and apoptosis in H9c2 cardiomyoblasts were studied at an increasing concentration from 0 to 100 µM. RESULTS: Resveratrol pretreatment with concentrations of 10, 20, and 50 µM inhibits autophagic apoptosis by increasing p-Akt and Bcl-2 protein levels in H9c2 cells. Interestingly, resveratrol treatment activates the Beclin-1, LC3, p62, and the lysosome-associated protein LAMP2a within 24 h of administration. CONCLUSIONS: These results suggest that resveratrol-regulated autophagy may play a role in degrading damaged organelles in H9c2 cells rather than causing apoptosis, and this may be a possible mechanism by which resveratrol protects the heart during CVD.